2014
DOI: 10.4103/0300-1652.132043
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dyslipidemia in pre-dialysis patients in south-west Nigeria

Abstract: Background:Majority of chronic kidney disease (CKD) patients are more likely to die of cardiovascular complications before reaching end stage renal disease. The Kidney Disease Outcomes Quality Initiative (K/DOQI) recommends that all CKD patients should be evaluated for dyslipidemia and for treatment to reduce the risk of cardiovascular events.Patients and Methods:A cross-sectional case control study to determine the frequency of occurrence of lipid abnormalities in patients with CKD and compare these abnormali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This fact draws attention, since excess body fat is associated with cardiovascular risk factors, such as metabolic syndrome, DM, hypertension, hypercholesterolemia and atherosclerosis. 34 Dyslipidemia is common in CKD and its presence can contribute to increase cardiovascular risk, 35 since elevated TG and reduced HDL-c are independent predictors of cardiometabolic episodes 36 . Regarding elevated LDL-c, data from the National Health and Nutrition Examination Survey (NHANES 1999(NHANES -2006 demonstrated a 46% prevalence of this lipid alteration in adults with stages 1-2 CKD and 80% with CKD stages 3 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…This fact draws attention, since excess body fat is associated with cardiovascular risk factors, such as metabolic syndrome, DM, hypertension, hypercholesterolemia and atherosclerosis. 34 Dyslipidemia is common in CKD and its presence can contribute to increase cardiovascular risk, 35 since elevated TG and reduced HDL-c are independent predictors of cardiometabolic episodes 36 . Regarding elevated LDL-c, data from the National Health and Nutrition Examination Survey (NHANES 1999(NHANES -2006 demonstrated a 46% prevalence of this lipid alteration in adults with stages 1-2 CKD and 80% with CKD stages 3 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of CVRF and CVD in CKD patients in SSA is limited. Few studies reported that the burden of CVRF and CVD is high in CKD patients in this setting and the care of these patients is largely in-Open Journal of Nephrology adequate and suboptimal [27] [28]. In Cameroon, CKD prevalence is high mainly due to hypertension, diabetes and chronic glomerulonephritis [29] [30].…”
Section: Introduction [1]mentioning
confidence: 99%
“…In other hand, 50% of renal patients were involving in dyslipidemia [7]. Another study showed that renal dysfunction was associated with both reduction in serum HDL concentration and increased circulating monocyte count [8]. While CKD is a global public problem, patients with CKD have higher risk of progression to ESRD.…”
Section: Introductionmentioning
confidence: 99%